2020
DOI: 10.3390/app10113688
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Characterization of Green Composites with Partially Biobased Epoxy Resin and Flaxseed Flour Wastes

Abstract: In the present work, green-composites from a partially biobased epoxy resin (BioEP) reinforced with lignocellulosic particles, obtained from flax industry by-products or wastes, have been manufactured by casting. In this study, the flaxseed has been crushed by two different mechanical milling processes to achieve different particle sizes, namely coarse size (CFF), and fine size (FFF) particle flaxseed flour, with a particle size ranging between 100–220 µm and 40–140 µm respectively. Subsequently, different loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…It is observed that the addition of short hemp fiber as reinforcement has a direct impact on the water absorption capacity of composite materials. As the amount of fiber in the structure increases, the ability of the composites to absorb water tends to increase as well, mainly due to the hydrophilic nature of natural fibers as a result of the large amount of -OH groups present in hemicellulose and cellulose that tend to interact with water molecules easily [71,72]. The incorporation of PP-g-MA in the structure of the composites is noteworthy since this agent has an inhibiting effect on the water absorption capacity.…”
Section: Water Uptake Properties Of the Recycled Polypropylene Sample And The Rpp/hemp Fiber Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the addition of short hemp fiber as reinforcement has a direct impact on the water absorption capacity of composite materials. As the amount of fiber in the structure increases, the ability of the composites to absorb water tends to increase as well, mainly due to the hydrophilic nature of natural fibers as a result of the large amount of -OH groups present in hemicellulose and cellulose that tend to interact with water molecules easily [71,72]. The incorporation of PP-g-MA in the structure of the composites is noteworthy since this agent has an inhibiting effect on the water absorption capacity.…”
Section: Water Uptake Properties Of the Recycled Polypropylene Sample And The Rpp/hemp Fiber Compositesmentioning
confidence: 99%
“…Figure 7a shows the obtained materials, and it is evident that the visual aspect significantly changed acquiring wood aspect. As can be seen in Figure 7b, the incorporation of SHF modified the color coordinates so that they acquired the appearance of woods like teak or eucalyptus [72,[76][77][78]. In this instance, rPP-H30-M took an appearance very similar to oak wood.…”
Section: Colorimetry Properties Of Rpp/hemp Fiber Compositesmentioning
confidence: 99%
“…Compared to inorganic fillers, the main advantages of natural fillers are their low cost, low density, renewal capacity, biodegradability, availability, and so on. [3][4][5] However, the lack of adhesion with polymer matrices presents a drawback for the widespread use of natural fillers in composites. The hydrophobic character of most polymers and the hydrophilic character of natural fillers negatively affect adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these voids in the internal structure of the composite materials enables water to enter, thus increasing their water absorption. [ 66 ] Another factor is the hydrophilic nature of the biofillers, due to the large number of hydroxyl groups present in PPF, belonging to phenols, proanthocyanidins, condensed tannins and fiber content (cellulose, hemicellulose and lignin), which promote water absorption by hydrogen bonding. [ 7,67,68 ] This effect is evident after the first week of immersion, especially in composites containing untreated PPF.…”
Section: Resultsmentioning
confidence: 99%